Application of nano based drug delivery channel against leukemia chemotherapeutic resistance - Rahul Bhattacharjee; Olabimtan Olabode H; Ochigbo Victor; Samuel Florence (Global Journal of Cancer Therapy - Peertechz Publications, 2021)
To the management of leukemia, traditional chemotherapy is characterized by repeated dosage, adverse side effects, disruption to the immune system and other organs with rapidly proliferating cells due to non-specific targeting, insolubility, and failure to attack the tumor center, low survival treatment impairments, and resistance from the targeted cancerous cells. The management of most anti-leukemic drugs would be improved if, through a suitable scientific process that can be released to their biological targets through technological manipulation at the nano-molecular dimension. Nanoparticles are increasingly being implemented and adopted in alleviating numerous constraints with the conventional technique for drug delivery with cancer therapy. With excessive drug localization and cell adhesion, nanotechnology has presented an opportunity to selectively secure easy links to cancerous cells as it is feasible to program nanoparticles such as gold to identify cancerous cells as well as provide selective and precise drug delivery mechanisms that prevent interplay with normal cells. This review outlook essentially illustrates the significance of nano-based anticancer therapy for active targeting, the drawbacks of traditional chemotherapy, the responsive pH existence of nano-based anticancer drugs with cellular delivery through a stabilized biocompatible carrier, the biochemical compositions of nano-structured media, existing methodologies for nano-based anticancer therapy (leukemia) formulation and recognition of gold nanoparticles as an ideal anticancer drug delivery material.